INDONESIAN SENTENCES ACQUISITION BY A THREE-YEAR-OLD CHILD - Enni Maisaroh (Universitas Potensi Utama, 2019)
It is about the Indonesian acquisition declarative sentences produced by a three-year-old child. The language acquisition study is able to tell us more information about development of language psychologically and intellectually on child. Relationship of surrounding and children affect them in using language. The objective of this study is to investigate the patterns of sentence on Indonesian declarative are acquired by the three-year-old child. The study is a case study, the data were a child’s utterances and the source of the data were taken from a child is three year old. The way of the researcher to collect sufficient data, the recorder was used for collecting the data. The child’s utterances were recorded every Sunday for three weeks. The outcome of this study found A three-year-old child was not able to acquire the complex grammatical. Of the six pattern proposed, he was just able to acquire three out of them, the running pattern, being pattern and doing/seeing pattern. On the other hand, he wasn’t able to acquire the pattern of giving/buying (ditransitive verb), the pattern of making/considering (complex-transitive verbs) and same verb, different pattern. But from those three declarative patterns acquired, a child also acquired more the sub-patterns. Meanwhile the process tells that the subjects’ sentence production basically influence by both nature process (that language is basically innate, that children were born with language acquisition device that children acquire grammar of language without adult’s instruction) and nurture process (that children’s task is learning how different words behave in sentence, categorizing together words that behave in similar ways and extracting the pattern that govern this behavior from the input that they hear around them).